Clinical Risk Factors for NonSalvageable Testis in Testicular Torsion Patients - Daryanto, Besut; Indradiputra, I Made Udiyana; Satyagraha, Paksi (International Journal of Psychosocial Rehabilitation, 2020)
This retrospective study was conducted to describe and analyze the clinical risk factors of non salvageable affected testis in pediatric and adult testicular torsion patients in Saiful Anwar Hospital Malang.Orchiectomy and contralateral orchidopexy were performed to 63 patients (90%) due to non-viable affected testis, with the left testis as the most commonly affected (48 patients/68.6%). It was found that symptom onset more than 6 hours was associated to increase the likelihood of non-salvageable testis/orchiectomy (odds ratio/OR 155; 95% confidence interval =11.9-2020.3, p0.05).The duration of symptoms until detorsion was the most important modifiable factor of salvageable testis in testicular torsion patient, hence immediate (